2014
DOI: 10.1007/s13277-013-1603-4
|View full text |Cite|
|
Sign up to set email alerts
|

The prognosis and clinicopathology of CXCR4 in gastric cancer patients: a meta-analysis

Abstract: The chemokine receptor 4 (CXCR4) has been widely investigated in diagnosis and prognosis of gastric cancer (GC). However, the impact of CXCR4 on GC patients remains controversial; Here, we conducted a meta-analysis to obtain the precise role of CXCR4 in GC prognosis and clinicopathology. Thirteen published studies with a total of 1,936 patients were included. Original data included the hazard ratio (HR) of overall survival (OS) and odds ratio (OR) in GC patients. We combined HR/OR with 95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Positive staining for CXCR4 was identified in 80% of the primary gastric tumor tissues (Han et al, 2014). CXCR4 expression in primary gastric carcinomas is associated with the development of peritoneal carcinomatosis and malignant ascites which contained high levels of CXCL12 (Yasumoto et al, 2006).…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Positive staining for CXCR4 was identified in 80% of the primary gastric tumor tissues (Han et al, 2014). CXCR4 expression in primary gastric carcinomas is associated with the development of peritoneal carcinomatosis and malignant ascites which contained high levels of CXCL12 (Yasumoto et al, 2006).…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
“…A meta-analysis by Han et al showed that CXCR4 expression is associated with poor prognosis in gastric cancer patients. In this study, OS was found to significantly correlate with CXCR4 expression, with the HR of 2.63 (95% CI: 1.69–4.09; P <0.0001), and a significant association was also detected between CXCR4 expression and tumor stage (odd ratio (OR): 0.52, 95% CI: 0.32–0.83; P = 0.007), depth of invasion (OR: 0.44, 95% CI: 0.27–0.73; P = 0.001), lymph node metastasis (OR: 2.30, 95% CI: 1.57–3.36; P <0.0001), and vascular invasion (OR: 0.72, 95% CI: 0.53–0.98; P = 0.04) (Han et al, 2014). Fakhari et al (2014) reported that Helicobacter pylori infection increased CXCL12 secretion by gastric epithelial cell line, upregulated CXCR4 expression in bone marrow-derived-mesenchymal stem cells, and enhanced their migration toward CXCL12 gradient.…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
“…High expression of CXCL12 is associated with reduced overall survival in GC patients (HR 2.08; 95% CI = 1.31-3.33; P = 0.0002) [73] . CXCR4 expression is associated with shorter overall survival (HR 2.63; 95% CI = 1.69-4.09; P < 0.001) [74] .…”
Section: Chemokinesmentioning
confidence: 99%
“…Oncotarget [28] FOXP3+ TILs (intra-tumoral) Tumour Biol [74] CXCL12 2.08 1.31-3.33 0.002 2017 Br J Cancer [73] MMPs MMP-2 1.92 1.48-2.48 < 0.001 2014…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…CXCR4 potentiates growth, angiogenesis/angiostasis, invasion/ metastasis and prognosis of various cancers, including esophageal cancer, renal cancer, breast cancer, colorectal carcinoma, glioma, gastric cancer and ovarian cancer [1][2][3][4][5][6][7][8]. CXCR4 is significantly associated with tumor stage, lymph node status, distant metastasis and poor survival [1,[3][4][5][6]8,9].…”
Section: Introductionmentioning
confidence: 99%